Bulk micromachining for SOI based microsystems using double side XeF2 etching. (23rd January 2008) - Bhaskar, Avinash K.; Packirisamy, Muthukumaran; Bhat, Rama B.
Microfabrication is pivotal in any microsystem synthesis. Even through silicon is the most common material used in the Micro Electro Mechanical System (MEMS) foundry, Silicon on Insulator (SOI) wafers are very promising for the fabrication of Micro Opto Electro Mechanical System (MOEMS) Devices such as micromirrors due to their better optical reflectivity, low residual stress and compatibility with silicon microfabrication processes. The present work explores the possibility of patterning and using controlled pulse etching method involving Xenon difluoride (XeF2) to etch SOI wafers to realise micromirrors. Pulse-etching method is proposed due to its better control and etching uniformity. This paper also presents the process flow for the fabrication of SOI based micromirrors through double side XeF2 micromachining which involves mask preparation, photolithography and pulse etching. The presented results also include etch characteristics obtained on SOI wafers.